Adaptive finite element simulation of chronoamperometry at microdisc electrodes - Harriman, K; Gavaghan, D; Suli, E (2003)
In this paper we shall introduce a transient finite element algorithm by considering the simplest problem of numerical simulation of the chronoamperometric current for an E reaction mechanism at a microdisc electrode. Such a numerical simulation is made difficult by the presence of a boundary singularity where the electrode meets the insulator (often known as the 'edge-effect') and by a time-singularity caused by the impulsive start of the experiment. We attempt to overcome these problems by using an adaptive finite element algorithm in which we derive an a posteriori bound on the error in the computed current. This is used to guide mesh refinement and adaptive time-stepping, resulting in a fully automated algorithm which is both accurate and efficient. © 2003 Elsevier Science B.V. All rights reserved.